2019
DOI: 10.1038/s41379-018-0157-9
|View full text |Cite
|
Sign up to set email alerts
|

Large cribriform growth pattern identifies ISUP grade 2 prostate cancer at high risk for recurrence and metastasis

Abstract: Invasive cribriform and intraductal carcinoma are associated with adverse clinical outcome in patients with Gleason score 7 prostate cancer. It is yet unclear whether invasive cribriform and intraductal carcinoma of the prostate both have independent prognostic value, or whether field size of invasive cribriform carcinoma has impact on disease outcome. Our objective was to determine the prognostic impact of intraductal and invasive cribriform prostate cancer histological subtypes in radical prostatectomies. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
129
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(137 citation statements)
references
References 29 publications
7
129
0
1
Order By: Relevance
“…Diolombi and Epstein [22] found 0.6% pelvic lymph node metastasis among 3235 men with GG2 Pca at RP without stratification for CR/IDC. In another GG2 RP cohort, lymph node metastasis were present in 12/228 (5.3%) patients with CR/IDC but in none of 192 men without CR/IDC [23]. Studies comparing the interobserver variability of both models, however, still have to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Diolombi and Epstein [22] found 0.6% pelvic lymph node metastasis among 3235 men with GG2 Pca at RP without stratification for CR/IDC. In another GG2 RP cohort, lymph node metastasis were present in 12/228 (5.3%) patients with CR/IDC but in none of 192 men without CR/IDC [23]. Studies comparing the interobserver variability of both models, however, still have to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, various studies demonstrated that GG2 patients with invasive cribriform and/or intraductal carcinoma have worse disease outcomes than those without 8,9,14,16,28,29 . Although it is generally accepted that GG2 patients have more aggressive disease than GG1 patients, it is unclear whether this is still the case when those with aggressive cribriform pathology are excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive and/or intraductal cribriform carcinoma, both also referred to as cribriform architecture, have been identified as pathological parameters for worse outcome in both biopsy and radical prostatectomy specimens 7–12 . Cribriform architecture has been associated with advanced tumour stage, biochemical recurrence, metastasis and disease‐specific death in GG2 patients 13–15 . Although patients with GG2 prostate cancer without cribriform architecture (GG2−) have favourable outcomes as compared with those with invasive and/or intraductal cribriform carcinoma (GG2+), it is unclear to what extent GG2− prostate cancer differs from GG1 prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the expansile cribriform pattern (Figure 1A) was associated with similar outcomes to Gleason pattern 5 carcinomas and was significantly linked to treatment failure, with a higher cumulative odds ratio of failure per added square millimeter of cribriform pattern than for any other type of Gleason pattern 4 4 . In another study that compared expansile cribriform to simple cribriform, the expansile cribriform pattern was associated with higher percentages of Gleason pattern 4, extraprostatic extension (EPE), and more frequent lymph node metastases, and was an independent predictor of BCR‐free survival 5 …”
Section: Introductionmentioning
confidence: 96%
“…The cribriform pattern, for example, has been associated with worse outcomes than other types of pattern 4 1,2 and is an independent parameter for biochemical recurrence (BCR) after prostatectomy 3 . Various studies have further subdivided the cribriform Gleason pattern 4 into two types, simple cribriform (also called small cribriform) and expansile cribriform (also called large cribriform), with the expansile cribriform pattern variously defined as large cribriform acini with greater than 12 lumen spaces 4 or as cribriform structures with a diameter of at least twice the size of adjacent normal glands 5 . In one study, the expansile cribriform pattern (Figure 1A) was associated with similar outcomes to Gleason pattern 5 carcinomas and was significantly linked to treatment failure, with a higher cumulative odds ratio of failure per added square millimeter of cribriform pattern than for any other type of Gleason pattern 4 4 .…”
Section: Introductionmentioning
confidence: 99%